A Subtitling Analysis Of Verbs And Verb Phrases In Divergent Movie By Erick Jiwono - Rosdiana, Dina, Dwi Haryanti, Dra. M. Hum., Dr, Siti Fatimah, S. Pd, M. Hum (2015)
This study aims at analyzing the subtitling analysis of verbs and verb phrase of Divergent movie from English into Indonesia, classify the translation shifts of verbs and verb phrase of Divergent movie and explain the translation equivalence of the subtitled. The research type is descriptive qualitative research. The writer uses documentation in process of collecting data. The data are identified using translation analysis theory according to A Linguistic Theory of Translation by Catford (1965). There are some steps of collecting data, namely: the writer watching the Divergent movie and identifying the verbs and verb phrase from the movie dialogue, marking verbs and verb phrase on the script, classifying the verbs and verb phrase, coding the data of verbs and verb phrase. The collected data are identified by using A Linguistic Theory of Translation by Catford (1965). The result of the research finding shows that firstly, the translation shift is divided into two types namely category shift and level shift. In this result, the category shift of verbs and verb phrases is divided into three kinds, they are class shift, intra - system shift, and structure shift. There are 102 of 255 data analysis of translation shift of verbs and verb phrases or the percentage of this analysis is 39,08%. Secondly, there are the equivalent and non equivalent translation. In this research, the writer finds that all of the data of verbs and verb phrases included in equivalent translation. It means that the data of this research is 100% equivalent. The result of this study shows that the translator makes an equivalent translation